2011
DOI: 10.1093/cvr/cvr083
|View full text |Cite
|
Sign up to set email alerts
|

A gain-of-function SNP in TRPC4 cation channel protects against myocardial infarction

Abstract: We provide evidence for the association of a TRPC4 SNP with MI in population-based genetic studies. The higher Ca(2+) signals generated by TRPC4-I957V may ultimately facilitate the generation of endothelium- and nitric oxide-dependent vasorelaxation, thereby explaining its protective effect at the vasculature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…5 On the basis of recent genome-wide association studies, calcium channels are implicated in the pathophysiology of BD, 18,19 and these channels also appear to be salient to CVD. 20,21 MDD and BD are the first and fourth most disabling conditions, respectively, among adolescents worldwide. 22 BD involves repeated episodes of mania/hypomania (elated or irritable mood together with other symptoms) that generally, but not always, alternate with episodes of depression (sadness or lack of interest/pleasure along with other symptoms).…”
Section: Circulationmentioning
confidence: 99%
“…5 On the basis of recent genome-wide association studies, calcium channels are implicated in the pathophysiology of BD, 18,19 and these channels also appear to be salient to CVD. 20,21 MDD and BD are the first and fourth most disabling conditions, respectively, among adolescents worldwide. 22 BD involves repeated episodes of mania/hypomania (elated or irritable mood together with other symptoms) that generally, but not always, alternate with episodes of depression (sadness or lack of interest/pleasure along with other symptoms).…”
Section: Circulationmentioning
confidence: 99%
“…Whether TRPC4 contributes to the repetitive Ca 2+ spikes arising in HUVECs both before (spontaneous) and after (histamine-evoked) tubule formation in a store-dependent or independent manner has yet to be elucidated [224] . A single nucleotide polymorphism in the TRPC4 gene has been associated with protection from myocardial infarction and results in a larger current density when the mis-sense channel is expressed in heterologous cell systems [266] . This feature is likely due to a less bulky Val-957, which favors TRPC4 insertion into the plasma membrane and its interaction with the catalytic site of the tyrosine kinase that phosphorylates the channel at Tyr-959 [266] .…”
Section: +(Rt-pcr)mentioning
confidence: 99%
“…A single nucleotide polymorphism in the TRPC4 gene has been associated with protection from myocardial infarction and results in a larger current density when the mis-sense channel is expressed in heterologous cell systems [266] . This feature is likely due to a less bulky Val-957, which favors TRPC4 insertion into the plasma membrane and its interaction with the catalytic site of the tyrosine kinase that phosphorylates the channel at Tyr-959 [266] . Less information is available on the role played by TRPC5 in ECs, where it may be constitutively open and also participate to ATP-induced Ca 2+ entry [267] .…”
Section: +(Rt-pcr)mentioning
confidence: 99%
“…This mechanism underlying protection is an improved endothelial function, but this needs more investigation. 29 In other study, photoparoxysmal responses (PPR) characterized by abnormal visual sensitivity of the brain to photic stimulation which is generally related to idiopathic generalized epilepsies (IGE) are related to various SNPs in the TRPC4 gene. 30 This relation was not significant after corresponding corrections, this trend toward relation of TRPC4 variants and PPR/IGE is of especial interest and deserves further investigation since it could be shown that TRPC4 is involved in numerous functions related with epilepsy.…”
Section: Trpc4 Channelsmentioning
confidence: 99%